PENERAPAN ARSITEKTUR HEALING ENVIRONMENT DALAM PERANCANGAN PUSAT PEMBINAAN DAN PEMBERDAYAAN PEREMPUAN DI KOTA MAKASSAR - Lukman, Fitria; Tauhid, Fahmyddin A'Raaf; Alfiah, Alfiah (The Department of Architecture, Faculty of Science and Technology, Universitas Islam negeri Alauddin Makassar, 2026)
The high rate of violence against women in Makassar City has caused various physical and psychological impacts on victims, including trauma, stress, anxiety, and decreased quality of life. Therefore, a facility that can provide protection, empowerment, and psychological recovery for women victims of violence is urgently needed. The purpose of this design is to create a Women’s Development and Empowerment Center in Makassar City using a healing environment approach, providing a safe, comfortable, and therapeutic space that supports users’ psychological recovery. The method used is a qualitative descriptive method through site observation, literature study, space requirement analysis, circulation analysis, and the application of the healing environment concept to site planning, exterior, and interior design. The design concept is implemented through the use of natural elements, green open spaces, healing gardens, natural lighting, natural ventilation, aromatherapy vegetation, and zoning arrangements consisting of public, semi-public, semi-private, and private areas to enhance both physical and psychological comfort for users. The design results show that applying the healing environment concept can create a more therapeutic, human-centered atmosphere that supports the emotional recovery of women victims of violence by integrating nature, comfortable circulation systems, and sensory elements that promote relaxation and reduce users’ stress levels.